Prevalence and Risk Factors of Cardiovascular Disease in Rheumatoid Arthritis Patients: A Comparative Analysis of Real-World Data - Tekeoglu S (International Journal of General Medicine)
Senem Tekeoglu1,2 1Internal Medicine, Rheumatology, Halic University Medical Faculty, Istanbul, Turkey; 2Rheumatology, Private Bahcelievler Memorial Hospital, Istanbul, TurkeyCorrespondence: Senem Tekeoglu, Internal Medicine, Rheumatology, Halic University Medical Faculty, 5. Levent Mahallesi, Istanbul, 34060, Eyupsultan, Turkey, Email senemtekeoglu@halic.edu.trPurpose: Rheumatoid arthritis (RA) is linked to cardiovascular disease (CVD), due to chronic inflammation and traditional CVD risk factors. This study evaluates CVD and related risk factors in RA patients compared to age and gender-matched controls without inflammatory diseases, and differences within RA patients with and without CVD.Patients and Methods: This retrospective case-control study reviewed medical records of 405 RA patients (cases) and 950 control patients who attended rheumatology clinics in two branches of a private hospital between January 2021 and January 2024 to assess cardiovascular disease prevalence and associated risk factors.Results: RA patients, with a mean age of 59 (± 23) years, disease duration of 89.5 months, and a female-to-male ratio of 4:1, exhibited a higher prevalence of CVD compared to controls (p = 0.01), despite similar classical risk factors. Logistic regression identified RA as an independent risk factor for CVD (p = 0.02, odds ratio = 1.9). RA patients with CVD were typically older males (p < 0.001), presenting with higher rates of hypertension (p < 0.001), hyperlipidemia (p < 0.001), diabetes (p = 0.002), and chronic kidney disease (p < 0.001). Arrhythmias (p < 0.001) and heart failure (p < 0.001) were prevalent among this subgroup, along with elevated creatinine levels and reduced glomerular filtration rates (p < 0.001 each). Treatment patterns indicated lower use of methotrexate (p = 0.003) and higher use of leflunomide (p = 0.02) among RA patients with CVD.Conclusion: CVD in RA patients is multifactorial, involving both chronic systemic inflammation and classical CVD risk factors. Further research is necessary to advance our understanding of CVD in RA patients and to optimize treatment strategies for improved outcomes.Keywords: Rheumatoid arthritis, cardiovascular diseases, comorbidity, mortality